Obstetric fistula: A challenge to public health - Dharitri Swain; Swayam Pragyan Parida; Saubhagya Kumar Jena; Mahasweta Das; Hrushikesh Das (Wolters Kluwer Medknow Publications, 2019)
Obstetric fistula (OF) is one of the most important consequences of a prolonged obstructed labor, a big issue for low-income countries (LICs) like India. The objective is to identify and explore the knowledge regarding OF as a public health problem in LICs from peer review literature. The PubMed, Google Scholar, and Science Direct databases were searched to identify the prevalence, risk factors, and management of OF in LICs. Quantitative evidence-based paper reviewed. Twenty-seven articles met the inclusion criteria. The 15 provided population-based OF prevalence data of OF and 12 provided risk factors and social causes of OF rates associated with the birth that caused an OF. OF has one of the big public health problems. There is a lack of scientific research on the prevalence and risk factors of OF in LICs. This review helps to eradicate or alleviate the problem of OF in LICs like India.